Value cocreation among spectators in professional spectator sports events: Scale development and effects of social media strategies. - Chen-Yueh Chen; Yi-Hsiu Lin; Che-Yi Yang; Ya-Lun Chou; Tzu-Yun Yeh (PLoS ONE)
The purposes of this paper are to develop measurement scale of value co-creation among spectators in professional spectating sporting events by means of Study I and to examine the effects of social media strategies on value co-creation among spectators through Study II. In Study I, a five-phase framework for developing a measurement scale is adopted including items generation, items refinement and edition, exploration of the latent factor structure of the scale and confirmation of reliability, examination of the structure of the factors, and scale validation. In Study II, four quasi-experiments are conducted to investigate the effects of electronic word of mouth, second screen, social media influencer promotion and online donation on value co-creation among spectators. The sample size for Study I and Study II is 830 and 993, respectively. Results obtained from Study I reveal three dimensions of value co-creation among spectators in the context of professional spectating sporting events: event atmosphere, word of mouth, and spectator interaction. Findings from Analysis of Covariance (ANCOVA) in Study II indicate that in Experiment I, positive electronic word of mouth does not help improve value co-creation among spectators while negative electronic word of mouth does decrease value co-creation among spectators. In Experiment II, the second screen under the condition of either positive or negative electronic word of mouth does not exert an influence on value co-creation among spectators. In Experiment III, the effect of social media influencer promotion on value co-creation among spectators is partially supported. In Experiment IV, under the condition of positive electronic word of mouth, the group of donation reveals greater mean score of event atmosphere than that of the counterparts for the group without donation. The findings of this study not only enrich sport management literature in terms of value co-creation, but also provide empirical evidence and practical implications for decision makers of professional spectating sporting events in terms of social media strategies.